Presentation, management and outcomes in acute pituitary apoplexy: a large single‐centre experience from the United Kingdom. (26th August 2013) - Bujawansa, S.; Thondam, S. K.; Steele, C.; Cuthbertson, D. J.; Gilkes, C. E.; Noonan, C.; Bleaney, C. W.; MacFarlane, I. A.; Javadpour, M.; Daousi, C.
Summary Objective To study the presentation, management and outcomes and to apply retrospectively the Pituitary Apoplexy Score (PAS) (United Kingdom (UK) guidelines for management of apoplexy) to a large, single‐centre series of patients with acute pituitary apoplexy. Design Retrospective analysis of casenotes at a single neurosurgical centre in Liverpool, UK. Results Fifty‐five patients [mean age, 52·4 years; median duration of follow‐up, 7 years] were identified; 45 of 55 (81%) had nonfunctioning adenomas, four acromegaly and six prolactinomas. Commonest presenting features were acute headache (87%), diplopia (47·2%) and visual field (VF) defects (36%). The most frequent ocular palsy involved the 3rd nerve (81%), followed by 6th nerve (34·6%) and multiple palsies (19%). Twenty‐three patients were treated conservatively, and the rest had surgery either within 7 days of presentation or delayed elective surgery. Indications for surgery were deteriorating visual acuity and persistent field defects. Patients presenting with VF defects (n = 20) were more likely to undergo surgery (75%) than to be managed expectantly (25%). There was no difference in the rates of complete/near‐complete resolution of VF deficits and cranial nerve palsies between those treated conservatively and those who underwent surgery. Endocrine outcomes were also similar. We were able to calculate the PAS for 46 patients: for the group treated with early surgery mean, PAS was 3·8 and for those managed conservatively or with delayed surgery was 1·8. Conclusions Patients without VF deficits or whose visual deficits are stable or improving can be managed expectantly without negative impact on outcomes. Clinical severity based on a PAS ≥ 4 appeared to influence management towards emergency surgical intervention.